2001
DOI: 10.1002/path.1016
|View full text |Cite
|
Sign up to set email alerts
|

The Ki‐67 protein interacts with members of the heterochromatin protein 1 (HP1) family: a potential role in the regulation of higher‐order chromatin structure

Abstract: The expression of the nuclear protein Ki-67 (pKi-67) is strictly correlated with cell proliferation. Because of this, anti-Ki-67 antibodies can be used as operational markers to estimate the growth fraction of human neoplasia in situ. For a variety of tumours, the assessment of pKi-67 expression has repeatedly been proven to be of prognostic value for survival and tumour recurrence, but no cellular function has yet been ascribed to the Ki-67 protein. This study shows that a C-terminal domain of pKi-67 (Kon21) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 41 publications
4
87
0
5
Order By: Relevance
“…A myocyte mitotic index of 0.0014% in control hearts and 0.013% to 0.015% in diseased hearts was determined by confocal analysis. 2 Those initial data were confirmed and amplified in an autopsy study of human hearts 3 in which actively dividing cardiomyocytes (evidenced by Ki67 expression, a nuclear antigen expressed in dividing cells 4 ) resulted in mitotic indices of 0.08% and 0.03% in the regions adjacent to and distant from the infarcts, respectively. In principle, mitotic figures in the heart could arise from preformed cardiomyocytes released from cell cycle inhibition or from resident cardiomyocyte precursors or stem cells that become activated.…”
Section: Introductionmentioning
confidence: 83%
“…A myocyte mitotic index of 0.0014% in control hearts and 0.013% to 0.015% in diseased hearts was determined by confocal analysis. 2 Those initial data were confirmed and amplified in an autopsy study of human hearts 3 in which actively dividing cardiomyocytes (evidenced by Ki67 expression, a nuclear antigen expressed in dividing cells 4 ) resulted in mitotic indices of 0.08% and 0.03% in the regions adjacent to and distant from the infarcts, respectively. In principle, mitotic figures in the heart could arise from preformed cardiomyocytes released from cell cycle inhibition or from resident cardiomyocyte precursors or stem cells that become activated.…”
Section: Introductionmentioning
confidence: 83%
“…This is also supported by the finding that pKi-67 binds preferentially to supercoiled chromatin rather than to single-or doublestranded DNA (MacCallum and Hall 2000). Moreover, a recent study has demonstrated that the small non-histone heterochromatin protein 1 (HP1) interacts with the C-terminal portion of pKi-67 (Kametaka et al 2002;Scholzen et al 2002). Therefore, pKi-67 appears to be an intrinsic tracer that can be used to localize a well-defined heterochromatin domain in proliferating cells and to study its 3D organization.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its transportation function, the chromosome periphery may also play active roles in chromosome structure. As an example, the chromosome peripheral protein Ki-67 is involved in the formation of higherorder chromatin structures (Takagi et al, 1999;Kametaka et al, 2002;Scholzen et al, 2002;Saiwaki et al, 2005). In addition, it has been speculated that the chromosome periphery is involved in the progression of mitosis, possibly by participating in the protection and stabilization of the chromosomes.…”
Section: Introductionmentioning
confidence: 99%